PENGARUH PIJAT BAYI TERHADAP KUALITAS TIDUR BAYI UMUR 0-6 BULAN DI DESA PASAR LATONG KECAMATAN LUBUK BARUMUN KABUPATEN PADANG LAWAS TAHUN 2019 - KUMALA SARI RAMBE (JURNAL ILMIAH SIMANTEK, 2019)
Baby massage is one of the oldest forms of therapy. Indonesian people have known massage since the days of our ancestors and passed on from generation to generation. Sleep is one form of baby's adaptation to the environment. Shortly after birth, babies usually sleep for 16-20 hours a day. Entering the age of 2 months the baby starts sleeping more nights than noon. Until the age of 3 months, newborn babies will spend about 15-17 hours of sleep, with the division of time 8 hours for naps and 9 hours for night sleep. Based on a preliminary study in the Posyandu of Latong Village Roses by interviewing 10 parents of infants 0-6 months, 8 parents who never massaged their babies said their babies often wake up at night and the amount of sleep is less than 11 hours per day.Determine the Level of Influence of Baby Massage on Sleep Quality in Infants 0-6 Months in Pasar Latong Village, Lubuk Barumun District, Padang Lawas Regency in 2019This type of research that will be used in this study is to use the pre experimental design method, with the type of pre test and post test one group design.Based on the results of the study above, researchers can draw some conclusions as follows: 1. The quality of sleep in infants aged 0-6 months carried out massage in Pasar Latong Village, Lubuk Barumun District, Padang Lawas Regency in 2019 is mostly good. 2. Sleep quality in infants aged 0-6 months who have not been massaged in Pasar Latong Village, Lubuk Barumun District, Padang Lawas Regency in 2019 is mostly bad. 3. There is the influence of baby massage with sleep quality babies aged 0-6 months where babies who get baby massage have a good sleep quality 15 times higher than babies who do not get baby massage.